2021
DOI: 10.31234/osf.io/eaz3k
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Anti-Asian Discrimination and Antiracist Bystander Behaviors amid the COVID-19 Outbreak

Abstract: Anti-Asian racism is a public health concern, and it has escalated during the coronavirus disease 2019 (COVID-19) outbreak. Bystanders—individuals who witness acts of racism—can help by discouraging perpetrations of discrimination (and other forms of interpersonal violence), offering help and support to victims, and reinforcing (antiracist) prosocial norms. Yet, little is known about who engages in antiracist bystander intervention behaviors in response to discriminatory events, and who engages in proactive by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 4 publications
0
10
1
Order By: Relevance
“…Even so, there are costs for confrontation (Gulker et al, 2013). Lui et al (2021) described the value of allyship based on bystander interventions for anti-Asian racism and acts of discrimination. Bystanders are peoplewho directly witness or become aware of acts of racism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even so, there are costs for confrontation (Gulker et al, 2013). Lui et al (2021) described the value of allyship based on bystander interventions for anti-Asian racism and acts of discrimination. Bystanders are peoplewho directly witness or become aware of acts of racism.…”
Section: Discussionmentioning
confidence: 99%
“…Bystanders are peoplewho directly witness or become aware of acts of racism. Bystanders can interrupt or challenge the perpetrators before or during a discriminatory act, physically defend the victims of attacks, seek help from authority and other people, comfort and support the victims, and speak out against the incidents or perpetrators afterwards (Lui et al, 2021, pp. 3–5).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a surge of racist incidents (e.g., physical assault, verbal harassment, or online racial discrimination) targeting individuals of Asian descent has been reported in the United States and globally since the outbreak of the COVID-19 pandemic, with over 1,800 reports in the United States alone over an 8-week period (Borja et al, 2020; also, see Cheah et al, 2020). A Pew survey indicated that since the outbreak of COVID-19, about 40% of Asian American adults reported that people acted uncomfortably around them, 31% experienced racial/ethnic slurs or jokes, and 26% feared physical attack (Ruiz et al, 2020).…”
mentioning
confidence: 99%
“…Recently, we have seen the normalization of hate speech (Opotow & McClelland, 2020), an increase in hate crimes (Potok, 2017), and the instigation of domestic terrorism threatening racialized groups (Bell, 2019). Almost half of White Americans and nearly one third of Black Americans hold pro-White bias and a negative bias toward Black Americans (Morin & Rohal, 2015), and 31% of Asian Americans report being subjected to racialized slurs and jokes since the beginning of the COVID-19 pandemic (Ruiz et al, 2020). However, psychologists often remain hesitant to directly attribute health inequities to racism and draw implicit rather than explicit conclusions about key drivers identified in their work.…”
Section: Racismmentioning
confidence: 99%